Interpretations of law and ethics in Muslim contexts - Khanbaghi, Aptin (Muslim civilisations abstracts., 2012)
This volume brings together some of the many unheard voices of scholars studying law and ethics within Muslim societies. It features over 200 abstracts with bibliographical details in three languages (English, Arabic and Turkish), giving access to information about original post-1800 scholarly publications from Muslim contexts in the fields of law and ethics from different Muslim societies. The volume highlights the diversity of interpretations of law and ethics across these societies and creates access to, and reinforces communication between, scholars and institutions where sharing of knowledge and information has often been hindered by language barriers. --jacket.